Design and optimization of a 3D printed soft gripper for urban farming - Tan, Edwyn Bing Liang (Nanyang Technological University, 2022)
Urban farming has been gaining popularity in recent years due to global food sustainability challenges. This solution, however, can be hard to adopt due to it being labor intensive and its associated high manpower costing. Automated harvesting, an alternative solution, has not been explored much due to the high cost and technology required. Therefore, the design, development and feasibility of a cost-effective 3D printable gripper which allows automated harvesting of fruits with minimal damage dealt to them will be the objective of the project. 3D printing has the advantage of rapid prototyping and in this project, we adopt the technology to aid in the design phase of the gripper. 3 prototypes’ designs were considered during the design and fabrication phase, after printing the prototypes undergo tests to determine the feasibility of the design. Prototype 1 was designed prior to having much knowledge regarding 3D printing, therefore, the design was not 3D printing friendly. After researching about 3D printing, prototype 2 was redesigned considering the factors of 3D printing such as the material, method of printing, duration of printing, etc. Prototype 2 was printed using polylactic acid material but it cracked during the bending of the fingers leading to a failure. On the other hand, prototype 3 was designed by reconsidering the material used and decided to use flexible materials like thermoplastic polyurethane (TPU). Prototype 3 was a success and proceeded through a series of tests to optimize the printing parameters and the final design. The use of 3D printing and TPU material showed promising results as the time required for designing was greatly reduced and TPU material allowed the fingers to be more flexible, serving the purpose as a soft gripper minimizing damage to the fruits that are harvested.